The role of Anika in managing their operation as insurance broker in Malaysia / Azaziah Romli - Romli, Azaziah (Faculty of Business and Management, 2010)
Anika Insurance Brokers Sdn Bhd (AIB) is the oldest insurance and reinsurance broker in Malaysia. AIB offer full range of insurance products services covering risks in Property, Liability and Casualty, Crime, Transport, Engineering, Construction, Personal Insurance, Reinsurance and Life or Employee Benefits and others. In addition, Anika is only insurance broker in Malaysia currently to be awarded the MS ISO 90001:2000 certificated. As insurance broker, AIB is one of the members of the Malaysian Insurance and Takaful Brokers Association (MITBA) which is the professional association for the insurance Broker in Malaysia.